Honey drop dead - Childs, Laura (Childs, Laura. Tea shop mystery ;, 2024)
"Theodosia's Honey Bee Tea was an elegant affair set in Charleston's new Petigru Park amid newly planted native grasses and a community beekeeping project. But when a phony beekeeper shows up and sprays toxic smoke at the guests, the party erupts in chaos. Worse yet, a shot rings out and Osgood Claxton III, candidate for state legislature, falls to the ground--dead. Holly Burns, the gallery owner who asked Theodosia to cater the tea, is understandably heartbroken. A man is dead, her guests are angry and injured, and the paintings that were on display are left in tatters. When the police don't seem to have a clue, when old-line politicos don't want questions asked, Holly begs Theodosia to run a shadow investigation and help restore her gallery's good name. Between hosting a Wind in the Willows Tea and a Glam Girl Tea, Theodosia questions everyone that had a bone to pick with Claxton. This includes Booker, an angry outsider artist; Lamar Lucket, Claxton's political opponent; and Mignon Merriweather, the dead man's soon-to-be ex-wife. But the investigation becomes a political hot potato following a second murder, the revelation of a messy affair, a chase through a swamp, and a vandalized shop." -- Provided by publisher.